Tfh1 Cells in Germinal Centers During Chronic HIV/SIV Infection - Velu, Vijayakumar; Mylvaganam, Geetha; Ibegbu, Chris; Amara, Rama Rao (Frontiers in Immunology, 2018)
T follicular helper CD4 cells (Tfh) are essential for the development and maintenance of germinal center (GC) reactions, a critical process that promotes the generation of long-lived high affinity humoral immunity. It is becoming increasingly evident that GC-Tfh cells are heterogeneous in nature with some cellular characteristics associated with a Th1, Th2, and Th17 phenotype. Emerging studies suggest that GC-Tfh cells are directed to differentiate into distinct phenotypes during chronic HIV/SIV infection and these changes in GC-Tfh cells can greatly impact the B cell response and subclass of antibodies generated. Studies in HIV infected humans have shown that certain Tfh phenotypes are associated with the generation of broadly neutralizing antibody responses. Moreover, the susceptibility of particular GC-Tfh subsets to HIV infection within the secondary lymphoid sites can also impact GC-Tfh/B cell interactions. In this review, we discuss the recent advances that show Tfh heterogeneity during chronic HIV/SIV infection. In particular, we will discuss the dynamics of GC-Tfh cells, their altered differentiation state and function, and their impact on B cell responses during HIV/SIV infection. In addition, we will also discuss the potential role of a recently described novel subset of follicular homing CXCR5+ CD8 T cells (Tfc) and their importance in contributing to control of chronic HIV/SIV infection. A better understanding of the mechanistic role of follicular homing CD4 and CD8 T cells during HIV/SIV infection will aid in the design of vaccines and therapeutic strategies to prevent and treat HIV/AIDS.